Comparing body temperature measurements using the double sensor method within a wearable device with oral and core body temperature measurements using medical grade thermometers—a short report - Eisenkraft, Arik; Goldstein, Nir; Fons, Meir; Tabi, Michael; Sherman, Anna Danielle; Ben Ishay, Arik; Merin, Roei; Nachman, Dean (Frontiers in Physiology, 2023)
Body temperature is essential for diagnosing, managing, and following multiple medical conditions. There are several methods and devices to measure body temperature, but most do not allow continuous and prolonged measurement of body temperature. Noninvasive skin temperature sensor combined with a heat flux sensor, also known as the "double sensor" technique, is becoming a valuable and simple method for frequently monitoring body temperature. Body temperature measurements using the "double sensor" method in a wearable monitoring device were compared with oral and core body temperature measurements using medical grade thermometers, analyzing data from two prospective clinical trials of different clinical scenarios. One study included 45 hospitalized COVID-19 patients in which oral measurements were taken using a hand-held device, and the second included 18 post-cardiac surgery patients in which rectal measurements were taken using a rectal probe. In study 1, Bland-Altman analysis showed a bias of -0.04 °C (0.34 – (-0.43) °C, 95% LOA) with a correlation of 99.4% (p < 0.001). In study 2, Bland-Altman analysis showed a bias of 0.0 °C (0.27 – (-0.28) °C, 95% LOA), and the correlation was 99.3% (p < 0.001). In both studies, stratifying patients based on BMI and skin tone showed high accordance in all sub-groups. The wearable monitor showed high correlation with oral and core body temperature measurements in different clinical scenarios.